Evaluación de la gestión administrativa y su incidencia en el desarrollo educativo de las escuelas Enrique Mora Sares, presidente Jaime Roldos Aguilera y 24 de Junio de la ciudad de Machala, provincia de El Oro período lectivo 2011-20112 y propuesta de un modelo gerencial desde la teoría de la complejidad y del liderazgo educativo en concordancia con el plan decenal de educación. - Pulla Vásquez, Mario Fabián (2014)
This study focuses on the managerial analysis that is currently public education administration, taking as a specific reference, the institutions investigated. They aim to present a proposal to develop a modern and innovative management that is reflected through efficient administrative management. It also seeks to determine the environmental factors that have contributed to the denial in management performance, affecting the management of financial resources. It is to present a model of modern management as a tool to contribute to the achievement of a successful management. In other words, it is a study of feasible project underpinned by attempts to solve the problems at management level by which crosses this public body. the need for a new style of administration that allows optimal management to maximize financial resources, allocated through the constitutional in the budget approved by the government arises.